Dynamic loading test and simulation analysis of full scale semi-active hydraulic damper or structural control. - Niwa, Naoki (Earthquake engineering & structural dynamics.)
A semi active hydraulic damper (SHD) for a semi-active damper system, which is useful for practical structural control especially for large earthquakes, has been developed. Its maximum damping force is set to 1 or 2 MN, and it is controlled by only 70 W of electric power. An SHD with a maximum damping force of 1 MN was applied to an actual building in 1998. This paper first presents the results of a dynamic loading test to confirm the control performance of the SHD. Next, an analytical model of SHDs (SHD model) is constructed with the same concept for two kind of SHDs based on the test results. Through simulation analyses of the test results using the proposed SHD model, the dynamic characteristics of the SHD can be well represented within practical conditions. Simulation analyses are also carried out using a simple structure model with the SHD model. It is shown that this SHD model can be used to precisely evaluate the control effect of the semi active damper system and is useful in practical SHD design under the applied conditions.